2020
DOI: 10.37992/2020.1103.128
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diversity analysis in rice (Oryza sativa L.) using SSR markers

Abstract: Rice is the most important staple food crop among the cereals and feeds more than half of the world's population. Assessment of genetic diversity is of utmost importance in rice breeding from the perspective of selection, conservation and proper utilization. The present study was undertaken with an objective to assess the genetic diversity among 27 rice cultivars with 12 SSR markers. The results revealed a total of 40 alleles were detected across 27 rice cultivars tested. PIC values varied widely among SSR loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…Bhattacharjee et al ( 2021 ) also reported marker-based grouping independent of geographical origin. The average PIC (0.55) and the number of alleles (4) were in close accordance with the reports of Tripathi et al ( 2020 ) who reported average alleles of 3.7 and average PIC of 0.56 in molecular diversity analysis of 27 rice cultivars using 12 SSR markers and Salem and Sallam ( 2016 ) who obtained average values of 4.5 and 0.57 for number of alleles per locus and PIC respectively in genetic diversity study of 22 Egyptian and exotic rice genotypes using 23 SSR markers. Whereas Pandita et al ( 2023 ), Akter et al ( 2022 ) and Bajracharya et al ( 2006 ) reported lower mean values than our findings for PIC and number of alleles per locus.…”
Section: Discussionsupporting
confidence: 91%
“…Bhattacharjee et al ( 2021 ) also reported marker-based grouping independent of geographical origin. The average PIC (0.55) and the number of alleles (4) were in close accordance with the reports of Tripathi et al ( 2020 ) who reported average alleles of 3.7 and average PIC of 0.56 in molecular diversity analysis of 27 rice cultivars using 12 SSR markers and Salem and Sallam ( 2016 ) who obtained average values of 4.5 and 0.57 for number of alleles per locus and PIC respectively in genetic diversity study of 22 Egyptian and exotic rice genotypes using 23 SSR markers. Whereas Pandita et al ( 2023 ), Akter et al ( 2022 ) and Bajracharya et al ( 2006 ) reported lower mean values than our findings for PIC and number of alleles per locus.…”
Section: Discussionsupporting
confidence: 91%
“…Huo et al (2021) stated that other types of repeat sequences in the flanking region could become a significant constraint in the primer design process. Moreover, the use of SSR primers, designed using the polymorphic dinucleotide SSR motifs was reported as effective in the date palm (Naeem et al 2018), oil palm (Zhou et al 2020b), chilli (Zhong et al 2021), tomato (Castellana et al 2020), rice (Tripathi et al 2020), and wheat (Haque et al 2021). Therefore, only dinucleotide repeats were further evaluated in this study.…”
Section: Simple Sequence Repeat (Ssr) Motifsmentioning
confidence: 99%